2011
DOI: 10.1097/eja.0b013e328343d524
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age and sex on the relationship between heart rate variability, haemodynamic variables and subjective measures of acute post-operative pain

Abstract: Acute pain influences the sympathovagal balance. This response is significantly influenced by age and sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…Although, it is not clear whether pain in the postoperative period affects HRV; some studies suggested that pain may influence HRV and the sympathovagal balance [27,28], and others have not been able to show this correlation [16,29].…”
Section: Discussionmentioning
confidence: 99%
“…Although, it is not clear whether pain in the postoperative period affects HRV; some studies suggested that pain may influence HRV and the sympathovagal balance [27,28], and others have not been able to show this correlation [16,29].…”
Section: Discussionmentioning
confidence: 99%
“…This discordance between subjective and objective measures is not only observed in stress research, but has also been highlighted in various other disciplines (for example, subjective pain and sleep experiences [15], [16]). Understanding the mismatch between subjective and objective ratings may help better understanding these various states, and eventually lead to improved interventions.…”
Section: Introductionmentioning
confidence: 96%
“…22,24,26,28,31,33,37,39 Transcutaneous oxygen, skin conductance, and the analgesia/nociception index (calculated from HR variability) have been assessed in patients experiencing pain with inconsistent conclusions. 23,27,31,32,34,38,[40][41][42] Patients with severe pain who show no hypertension or tachycardia to substantiate their pain intensity might not receive the aggressive pain treatment they warrant. Our study aimed to determine whether vital signs are associated with pain intensity levels in both the ED population and a subgroup of patients with diagnosed conditions recognized to produce significant pain.…”
Section: Introductionmentioning
confidence: 99%